Clinical aspects of mastication myalgia—an overview - Barjandi, Golnaz; Svedenlöf, Johanna; Jasim, Hajer; Collin, Malin; Hedenberg-Magnusson, Britt; Christidis, Nikolaos; Ernberg, Malin (Frontiers in Pain Research, 2024)
Mastication myalgia is the most common cause of non-odontogenic pain in the orofacial region and is often associated with a reduced quality of life. The purpose of this review is to provide an overview of the clinical aspects of myalgia based on available research. The review includes epidemiological, diagnostic, and etiological aspects. In addition, the potential risk factors related to the transition from acute to chronic myalgia are explored and treatment strategies are presented for its management. As a result, this review may increase clinical knowledge about mastication myalgia and clarify strategies regarding prevention, diagnostics, and management to improve prognosis and reduce patient suffering.